Cultura organizacional, compartilhamento do conhecimento, habilidades profissionais e seus efeitos no desempenho organizacional em uma IFES - NOGUEIRA, Nathalia Maciel (Universidade Federal do Pará, 2024)
This study started from a literature review to examine the relationship between Organizational Culture, Tacit and Explicit Knowledge Sharing, and Professional Soft Skills and Hard Skills, investigating their impacts on Organizational Performance, proposing a conceptual model that evidences the relationship that was empirically tested in a federal institution of public higher education of reference, using the path analysis model. The analysis validated the hypotheses formulated and demonstrated that tacit knowledge sharing has a partial mediating effect on the relationship between organizational culture and performance. This study will contribute theoretically with a little-explored approach on the connection between knowledge sharing and professional skills, with a proposition of the concept of skill, and with the strengthening of the approach to building a culture of knowledge sharing in organizations. Its managerial implications, on the other hand, consist of management's investment in knowledge-sharing strategies and practices for the success of organizational performance.